Joint Precoder and Window Design for OFDM Sidelobe Suppression - Khawar Hussain; R. López-Valcarce (IEEE Communications Letters, 2022)
Spectral precoding and windowing are two effective approaches to reduce out-of-band radiation (OBR) in multicarrier systems. Their performance comes at the price of reduced throughput and additional computational complexity, so there is strong motivation for simultaneously using both techniques. We present a novel design that jointly optimizes the precoder and window coefficients to minimize radiated power within a user-selectable frequency region. Results show that the proposed design achieves a better OBR/throughput/complexity tradeoff than either of these individual techniques separately.
Keywords: rodin; spectrum shaping